A One-Year Cross Sectional Analysis of Emergency Medical Services Utilization and Its Association with Hypertension in Pregnancy. (2nd November 2022) - Hutchcraft, Megan L.; Ola, Oluwabusola; McLaughlin, Eric M.; Hade, Erinn M.; Murphy, Andrew J.; Frey, Heather A.; Larrimore, Ashley; Panchal, Ashish R.
Abstract: Objective: To evaluate the prehospital obstetric population that utilizes emergency medical services (EMS) and their association with hypertensive disorders of pregnancy. Methods: We conducted a retrospective evaluation of one year of all medical calls from a large, municipal, midwestern fire department. Inclusion criteria included all pregnant patients transported to a hospital by EMS. Descriptive statistics were calculated to evaluate prehospital event information (e.g., zip code, time, and duration of call), patient characteristics, and clinical management data regarding blood pressure. Census data were used to compare neighborhood information with poverty rates. Results: Of the 1, 575 identified patients, 64.4% (1015/1575) presented with obstetric complaints, 57.4% (700/1220) were in their third trimester and 72.7% (686/944) were multiparous. The median call duration was 17 (interquartile range 12–22) minutes. In the areas where EMS usage was highest, one quarter of individuals lived below the poverty level. Of the studied population, 32.0% (504/1575) were found to be hypertensive; 14.9% (75/504) of hypertensive patients were found to have severe hypertension. Only one patient (1/1575, 0.06%) presented with a chief complaint of hypertension; the rest were discovered by EMS. The highest rates of hypertension were noted in wealthier areas of the city. Patients with severe hypertension were more likely to present with seizures, consistent with eclampsia. Conclusion: Hypertension is common in the obstetric population using EMS. Prehospital management of hypertensive disorders of pregnancy may focus on identification and treatment of severe pre-eclampsia or eclampsia. Areas with longer call times may consider treatment of severe hypertension. Prehospital treatment of hypertensive disorders of pregnancy could be optimized.